MADANIYAT VA SAN’AT SOHASIDA KREATIV TADBIRKORLIK FANI NAZARIYASI VA AMALIYOTINING SHAKLLANISHI - Sh.Salaydinov, B.; Qolqanatov, A.N. (SCIENCE and SOCIETY, 2022)
This article discusses the role and importance of entrepreneurship, especially creative entrepreneurship in the arts and culture. In the New Uzbekistan, under the leadership of President Sh. Mirziyoyev, scientific research has been conducted on new reforms and changes, opportunities. Emphasis is placed on the importance of teaching entrepreneurship to young people in the field of education.